Isolation, characterisation and synthesis of insecticidal natural products of the Myrtaceae family - Beddie, David G. (1998)
New insecticidal natural products are required to find compounds with higher intrinsic activities to lower field application rates, and with novel modes of action to combat insect pest species which have developed resistance to current commercial insecticides.